Citra Merek terhadap Kepercayaan Konsumen Pada Keunggulan Produk Kosmetik MS Glow - Nurhanifah, Nurhanifah; Rkt, Lana Sari; Nanda Nst, Anggun Dwi; Nadila, Nurhaida; Nainggolan, Annisa Erina; Ramadhani, Izky Putri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The goal of this study is to find out how much consumers trust Ms. Glow's beauty products, which has a big impact. This demonstrates that customers consider Ms. Glow's beauty products to be superior to those of rival brands or other brands. The Ms. Glow brand's products, according to customers, are of high quality and have a positive effect on the face when used. The business world always evolves over time, especially the cosmetic or beauty industry, which has become a necessity for every human being, both men and women, according to the explanation of the relationship or influence of brand image with brand loyalty and consumer trust with brand loyalty. The marketing communication strategies in this study start with marketing strategies based on the four Ps—product, price, places, and promotion. the kinds of promotions that were done and how satisfied customers were. The author employs a qualitative approach, and the author of this study employs a qualitative approach to explain the collected data. Keyword: Ms Glow, Effect of good image, Marketing Communication Strategy, Marketing Effectiveness